Physicians’ Legal Responsibility According to the High Council of Health - Gündoğmuş, Ümit Naci; Bilge, Yaşar; Kendi, Özer; Hancı, İsmail Hamit (The Bulletin of Legal Medicine, 1997)
In this study, 532 cases have been reviewed in the High Council of Health. Most of the physicians were obstetricians and surgeons. It is determined that 305 physicians (57.33%) were not responsible of the consequences while 186 (34.96 %) physicians (7.71%) were found guilty according to the articles 455 or 459 of the Turkish Penal Code and. 41 (7.71%) physicians were guilty of neglecting their duties and disobeying the rules. Keywords: Physician responsibility, malpractice.